Synthesis and Characterization of Cobalt/Aluminosilicate as Fischer-Tropsch Catalyst - Bahri, Syamsul
Nowadays, petroleum needs as a fuel is increasing significantly. This led to the development of an altenative fuel sources. Fischer-Tropsch (FT) catalyst is one of the catalysts used to produce hydrocarbon through the conversion of syngas (H2 and CO). In this research, cobalt based FT catalyst with amorphous aluminosilicate as a supporting material (Co/SiO2/Al2O3) was synthesized, characterized, and activity test. Amorphous aluminosilicate is one of the supporting material which is has a large surface area, so it could be a good supporting material for dispersing the active site of cobalt catalyst. Amorphous aluminosilicate was synthesized by reacting Al(OH)3 as an alumina source, tetraethyl orthosilicate (TEOS), as a silica source, NaOH for increasing reactant solubility, and water for hydrolysis and also as a solvent. Co/SiO2/Al2O3 was synthesized with two methods, one-stage and two-stage. In one-stage method, cobalt nitrate solution was mixed directly with Al(OH)3, TEOS, NaOH, and water at 298 K, while in two-stage method, cobalt nitrate solution was added to aluminosilicate with wetness incipient impregnation technique at 373 K. Amorphous aluminosilicate and catalyst which is synthesized with one-stage method (catalyst 1) and two-stage method (catalyst 2), were characterized using X-Ray Diffraction (XRD), N2 physisorption with BET method, and Scanning Electron Microscope (SEM). XRD diffractogram showed that aluminosilicate, catalyst 1, and catalyst 2 has an amorphous structure. BET surface area of aluminosilicate is 102 m2/g, catalyst 2 is 87 m2/g, and catalyst 1 is 78 m2/g. Synthesized catalysts were tested using fixed bed type reactor with 1 atm pressure at 473 K, ratio of CO:H2 1:2, and flow rate around 15 mL/minute. Activity of catalyst 1 and 2 was expressed in % conversion of CO, about 14,2% and 5,2 %, respectively.